The outlaws Scarlett and Browne - Stroud, Jonathan (New York : Alfred A. Knopf, 2021)
On the run from her latest bank robbery, Scarlett McCain comes to the rescue of Albert Browne, the sole survivor of a horrific accident, and soon learns he may be the most dangerous threat of all.
700L
Keywords: Outlaws -- Juvenile fiction; Fugitives from justice -- Juvenile fiction; Criminals -- Juvenile fiction; Bank robberies -- Juvenile fiction; Secrecy -- Juvenile fiction; Monsters -- Juvenile fiction; England -- Juvenile fiction; Fantasy fiction